Adopsi Platform Digital dalam Pengembangan Kapasitas Usaha Mikro, Kecil dan Menengah di Daerah Khusus Ibukota Jakarta - Bambang Irawan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The adoption of digital platforms by MSMEs in Indonesia is still very low. This can be due to the lack of capacity of MSMEs to adapt to digital technology. There are three main problems related to the capacity of MSMEs in dealing with digital platforms, namely financial resources, business operations, and business expansion. The purpose of the research is to analyze the digital platform model that can develop the capacity of MSMEs as business entities, especially related to financial resources, business operations, and business expansion. The research method used is netnography by presenting a new approach to conducting ethical and thorough ethnographic research that combines archival data and online communication, participation and observation, with digital data collection and networks. Informants in this study consisted of digital platform service providers, users, and regulators. There were fourteen informants involved in this study spread across two provinces, namely the Special Capital Region of Jakarta and Banten. Analysis of the data used is conceptually clustered matrices (matrices grouped conceptually) which are arranged to unite the main roles, research subtopics, concepts or themes together for documentation. The results of the study indicate that MSME capacity development in the adoption of digital platforms in terms of financial resources includes access to capital, preparation of financial reports and the use of accounting application platforms. In terms of business operations, it includes Human Resources management, payment systems and logistics management. As for business expansion, it includes digital marketing and online markets.